Interaction of an esophageal MEG protein from schistosomes with a human S100 protein involved in inflammatory response - Orcia, Débora; Zeraik, Ana Eliza; Lopes, José L.S.; Macedo, Joci N.A.; Santos, Clarissa Romano dos; Oliveira, Katia C.; Anderson, Leticia; Wallace, B.A.; Verjovski-Almeida, Sergio; Araujo, Ana P.U.; DeMarco, Ricardo (Biochimica et biophysica acta. General subjects, 2017)
The Micro-Exon Gene-14 (MEG-14) displays a remarkable structure that allows the generation of antigenic variation in Schistosomes. Previous studies showed that the soluble portion of the MEG-14 protein displays features of an intrinsically disordered protein and is expressed exclusively in the parasite esophageal gland. These features indicated a potential for interaction with host proteins present in the plasma and cells from ingested blood. A yeast two-hybrid experiment using as bait the soluble domain of Schistosoma mansoni MEG-14 (sMEG-14) against a human leukocyte cDNA library was performed. Pull-down and surface plasmon resonance (SPR) experiments were used to validate the interaction between sMEG-14 and human S100A9. Synchrotron radiation circular dichroism (SRCD) were used to detect structural changes upon interaction between sMEG-14 and human S100A9. Feeding of live parasites with S100A9 attached to a fluorophore allowed the tracking of the fate of this protein in the parasite digestive system. S100A9 interacted with sMEG-14 consistently in yeast two-hybrid assay, pull-down and SPR experiments. SRCD suggested that MEG-14 acquired a more regular structure as a result of the interaction with S100A9. Accumulation of recombinant S100A9 in the parasite's esophageal gland, when ingested by live worms suggests that such interaction may occur in vivo. S100A9, a protein previously described to be involved in modulation of inflammatory response, was found to interact with sMEG-14. Our results allow proposing a mechanism involving MEG-14 for the parasite to block inflammatory signaling, which would occur upon release of S100A9 when ingested blood cells are lysed. •Interaction of a S. mansoni MEG and a human immune-regulatory protein is described.•Structural changes are detected when MEG-14 interacts with S100A9.•MEG-14 interacts with S100A8/A9 dimer with lower affinity than with S100A9 homodimer.•Human S100A9 specifically accumulates in the parasite esophagus when ingested.